Mouse models of patent ductus arteriosus (PDA) and their relevance for human PDA. Issue 3 (14th August 2021) - Yarboro, Michael T.; Gopal, Srirupa H.; Su, Rachel L.; Morgan, Thomas M.; Reese, Jeff
Abstract: The ductus arteriosus (DA) is a unique fetal vascular shunt, which allows blood to bypass the developing lungs in utero. After birth, changes in complex signaling pathways lead to constriction and permanent closure of the DA. The persistent patency of the DA (PDA) is a common disorder in preterm infants, yet the underlying causes of PDA are not fully defined. Although limits on the availability of human DA tissues prevent comprehensive studies on the mechanisms of DA function, mouse models have been developed that reveal critical pathways in DA regulation. Over 20 different transgenic models of PDA in mice have been described, with implications for human DA biology. Similarly, we enumerate 224 human single‐gene syndromes that are associated with PDA, including a small subset that consistently feature PDA as a prominent phenotype. Comparison and functional analyses of these genes provide insight into DA development and identify key regulatory pathways that may serve as potential therapeutic targets for the management of PDA. Key Findings: Mouse models of patent ductus arteriosus (PDA) are informative for human PDA. Human single‐gene disorders with a PDA phenotype reveal interacting networks that contribute to regulation of DA patency and closure. Cross‐species correlations identify pathways of interest for development of PDA therapeutics.